A ANALISIS HUBUNGAN KEBIJAKAN PEMERINTAH TERHADAP KESEJAHTERAAN MASYARAKAT MISKIN DI KECAMATAN TANJUNG REDEB KABUPATEN BERAU - Indriani, Ira (ECO-BUILD, 2017)
Analysis of Government Policy Relation to the Prosperity of the Poor in Tanjung Redeb, Berau (Study of Direct Cash Assistance Program Policy "BLT").             The purpose of this study is to obtain information on Government Policy Relation in the form of Direct Cash Assistance (BLT) to the Wellbeing of the Poor in Tanjung Redeb, Berau.             Based on the results of the research note that the price of empirical rs smaller than the rs table is -0.058 <0.380, means there is no relationship between Government Policy in the form of Direct Cash Assistance with the Welfare of the Poor in the Tanjung Redeb Berau, thus the hypothesis is rejected.